Living by the pen : women writers in the eighteenth century - Turner, Cheryl, 1955- (Routledge, 1992)
"Based on a substantial listing of novels, authors and publication details from 1696 to 1796, Living by the Pen traces the pattern of growth of women's fiction and offers a persuasive explanation for the remarkable rise of women writers during this period. Professional novelists are identified and the book breaks new ground by exploring this aspect of women's writing in relation to the world of publishing. The coverage is broad, taking into account seventeenth-century antecedents, the occupation structure for women, the writers' relationship with their publishers, methods and levels of payment, the readership, access to women's fiction through libraries and magazines, and the writers' use of other genres to support their literary careers"--Jacket